Classification in the diagnosis and treatment of organ damage caused by urogenital trauma in children - Cengiz Güney; Abuzer Coşkun (Archive of Urological Research - Peertechz Publications, 2020)
Background: This study aimed to determine the characteristics of the urogenital traumas that constitutes a small part of children who were admitted to the emergency department, the classification of the injured organ, the conditions associated with the diagnosis and treatment. Material and Method: This retrospective cohort study included 254 patients younger than 18years of age who were admitted to the emergency department due to urogenital trauma between January 2014 and December 2018. Of these, 195(76.78%) were male, with a mean age of 8years (range, 1-15years). The demographic characteristics of these patients, types of trauma, examination results, classification of injured organs, diagnosis and treatment results were evaluated.  Result: Of the patients, 241(94.88%) were blunt, 10(3.93%) were penetrating and 3(1.18%) were with iatrogenic trauma. Of the cases of trauma, 146(57.5%) were falling from a height lower than one meter, 23(9.1%) were fall from a height higher than one meter, and 38(17.3%) were inside and outside of a car traffic accident, 10(3.93%) were sharp object injury. 28(11%) patients had a kidney, 9(3.5%) had a ureteral, 24(9.4%) had bladder and 20(7.8%) had a urethral injury. 17(6.7%) of the cases were operated due to various reasons. The pelvic fracture was detected in all bladder injuries. Hematuria was seen in all cases. Conclusion: Isolated urogenital traumas are rare and often accompany multiple organ injuries. Minor and major traumas are observed in the urogenital system in pediatric patients exposed to trauma. Urogenital traumas can also be seen in minor traumas. A thorough examination is required to avoid being overlooked.